Inside Back Cover: Quantum‐Dot Fluorescence Lifetime Engineering with DNA Origami Constructs (Angew. Chem. Int. Ed. 4/2013). Issue 4 (2nd January 2013) - Ko, Seung Hyeon; Du, Kan; Liddle, J. Alexander
<x xml:space="preserve">Abstract</x> The lifetime of quantum dots has been controlled by varying the geometrical configuration of quantum‐dot–gold nanoparticle (AuNP) conjugates on DNA origami templates. In their Communication on page 1193 ff., J. A. Liddle et al. describe a strategy to manipulate quantum‐dot lifetimes. Making measurements with a 3D single‐molecule tracking system, which enables the DNA construct to be kept in its native state in solution, the size, number, and spacing of the AuNPs are found to be the critical factors.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>